Volar-Dorsal Arthroscopic Repair for Scapholunate Ligament Injuries: A Case Series and Treatment Algorithm - Chambers, Spencer B.; Cooke, Hayden L.; Suh, Nina; Gottschalk, Michael B.; Wagner, Eric R. (Journal of wrist surgery, 2025)
Scapholunate interosseus ligament (SLIL) disruption is a challenging injury that presents with varying degrees of severity. The gold standard diagnosis is arthroscopic evaluation of the SLIL, but treatments have traditionally been performed with open surgical technique. This offers powerful correction, but outcomes are inconsistent, and postoperative stiffness is common. There is a paucity of methods for the management of mild SLIL instability, and the morbidity of open techniques may be difficult to justify in these situations. The development of arthroscopic techniques has expanded options to include repair while minimizing soft tissue disruption. This study presents an arthroscopic algorithm for the treatment of predynamic SLIL instability without radiographic deformity, with a case series demonstration of a dorsal and combined volar-dorsal repair. Following institutional review board approval, eight patients with clinical symptoms of SLIL injury who underwent diagnostic arthroscopy between November 2021 and July 2023 were identified for inclusion in our retrospective review. Repair techniques, including dorsal capsuloligamentous, as well as combined volar-dorsal suture arthroscopic repair, were performed based on injury severity in accordance with the European Wrist Arthroscopy Society (EWAS) grading system, including patients with grade 3 injuries. Pre- and postoperative range of motion, patient-rated outcomes measures, and radiographic metrics were assessed for all patients. Patients with scapholunate diastasis were excluded from this study and treated with alternative interventions. Median age of the population was 29.5 years, and included six right-sided and two left-sided injuries. Mean time to follow-up was 18.9 months. No patients presented with dorsal intercalated segment instability, and there was minimal change in alignment and scapholunate gapping postoperatively. Following the intervention, patients had excellent subjective function and range of motion. We describe a simple and effective suture-based arthroscopic capsuligamentous repair to treat SLIL injuries that are EWAS grade IIIA to C that resulting in excellent postoperative motion, function, and reduction of pain. Level IV/Therapeutic.